RANCANG BANGUN SISTEM INFORMASI INVENTORY PADA TOKO INDAH BARU - Aryanto; Wijaya, Setiawan Ardi; Silpandi, Dimas; saskia, ananda; Mihardi, Hansen; Wiyrabawa Kainna Putra Rachman (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2024)
Toko Indah Baru is a store specializing in various plastic goods for the industrial sector. The store caters to both small and large purchases. However, in its current business process, Toko Indah Baru still relies on manual systems, which have several drawbacks. One of them is the conventional method of recording goods and manually storing data using Microsoft Excel. To address these issues, a design and development of a web-based Inventory Information System application is proposed for Toko Indah Baru. The development methodology chosen for this project is the SDLC model waterfall. The proposed system aims to streamline inventory management processes, improve accuracy in recording and tracking goods, and enhance overall operational efficiency for Toko Indah Baru. By transitioning from manual methods to an automated web-based system, the store can expect to see significant improvements in inventory control and data management.